Employee Competency Management Initiative: A Literature Review (International Journal of Scientific Research and Management (IJSRM), 2022)
This paper discussed the concept of employee competency management initiatives. The paper highlighted particularly on three competency management initiatives – employee training, workplace mentoring and coaching. The paper is theoretical and as such draws its significance from its focus on the need for flexible and fluid employee competency initiatives given the changing dynamics and features of the work and business environment. This position is also hinged on the observed challenges of change and the imperatives for organizational learning and management re-orientation in line with the shifts in the market and the global community. The study concludes that the adoption and application of competency initiatives should begin with the specific needs of the organization as well as the specification of its goals. The design and features of competency management initiatives such as employee training, workplace mentoring and coaching, premised on the specifications of the organizations own particular experiences and expectations will offer more focus and will be more effective in addressing the organizations own unique or particular challenges and problems